A simple pyrene-pyridinium-based fluorescent probe for colorimetric and ratiometric sensing of sulfite. (September 2015) - Xu, Guanshu; Wu, Huan; Liu, Xingang; Feng, Ruokun; Liu, Zhanxiang
Abstract: The fluorescent probe is constructed by incorporating an α, β-unsaturated pyridinium to a pyrene fluorophore. The chemodosimeter has shown a selective and sensitive response to sulfite anion over other various anions and biological thiol through a Michael addition of the sulfite to the alkene of the probe. Meanwhile, it can be easily observed that the color of the probe for sulfite changes from yellow to colorless by the naked eye, and from yellow to blue under UV lamp immediately after the sulfite is added. Graphical abstract: The fluorescent probe is constructed by incorporating an α, β-unsaturated pyridinium to a pyrene fluorophore. The chemodosimeter has shown a selective and sensitive response to sulfite anion over other various anions and biological thiol through a Michael addition of the sulfite to the alkene of the probe. Highlights: The probe is combining an α, β-unsaturated pyridinium to a pyrene fluorophore. A colorimetric and ratiometric fluorescent probe for SO 3 2− with good sensitivity. The probe is easy-to-make. The sensor is suitable for detection of SO 3 2− by simple visual inspection.